2012
DOI: 10.12659/ajcr.882472
|View full text |Cite
|
Sign up to set email alerts
|

Complete spontaneous improvement of non-displaced femoral neck fracture without any surgery modality

Abstract: SummaryBackground:Fracture of the femoral neck is still a medical dilemma due to high rates of complications and the choice of treatment. Although rigid internal fixation with cannulated screws through open or percutaneous approaches is the traditional treatment for undisplaced fractures (Garden type I and II) to avoid secondary displacement, considerable controversy still exists regarding the rate of this problem, thus it seems that a new trend in conservative management of this types of femoral neck fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“… 3 ) The occurrence of fractures in the proximal femoral region will continue to increase. 1 , 2 , 6 , 7 , 17 ) These growing numbers are associated with problems related to osteoporosis, especially among elderly patients. 4 , 18 ) The long period of bed rest during conservative treatment can lead to walking disability, sarcopenia, frailty, and other complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 ) The occurrence of fractures in the proximal femoral region will continue to increase. 1 , 2 , 6 , 7 , 17 ) These growing numbers are associated with problems related to osteoporosis, especially among elderly patients. 4 , 18 ) The long period of bed rest during conservative treatment can lead to walking disability, sarcopenia, frailty, and other complications.…”
Section: Discussionmentioning
confidence: 99%
“…A previous case report described a patient with a non-dislocated femoral neck fracture who achieved bone union and became able to walk after 4 weeks of bed rest. 2 ) Another case report described a patient with a dislocated femoral neck fracture who did not obtain bone union but was able to walk after 3 weeks of bed rest led to decreased pain. 18 ) However, conservative treatment is realistic in older patients with a femoral neck fracture and severe underlying diseases like the present patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the authentic displacement of the femoral head is in 3D reconstruction offers advantages to the 2D approach and should be further investigated. 33 …”
Section: Discussionmentioning
confidence: 99%
“… 34 36 For instance, Gose et al found that 3D reconstructions was beneficial for the analysis of the femoral offset, the neck-shaft angle and the femoral anteversion of individuals with cerebral palsy, 34 while Li et al found that 3D reconstructions were useful for measuring the antero-lateral coverage of femoral head. 33 It is our belief that 3D CTs are the most accurate and direct method available for the assessment of spatial displacement in femoral head fractures.…”
Section: Discussionmentioning
confidence: 99%